Studi Legalitas Saksi Syahadah Al-Istifadah Dalam Pembuktian Perkara Itsbat Nikah: Pendekatan Maqashid Syari’ah - Syafruddin Syam; Rizki Muhammad Haris; Fachruddin Zakarya (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2022)
The prolonged conflict situation and the tsunami natural disaster in Aceh, resulted in the need for more progressive and philosophical legal reasoning to answer existing legal needs. Formal rules that apply legally are not sufficient conditions to explore legal justice. This is a juridical issue at the Syar'iyah Court. There needs to be legal findings in the midst of a society that is all squeezed and difficult. Among the legal issues that must be answered is how the marriage status was determined during the conflict, which was generally not recorded, plus the number of key witnesses who died during natural disasters. This is a challenge at the Meulaboh Syar'iyah Court in the case of itsbat marriage by imposing a witness known as Syahadah al-Istifadah or in customary legal nomenclature called Testimonium de Auditu. This article is a field research approach to civil law laws, civil law books, and Islamic books, especially focused on Islamic fiqh which discusses "Shahadah Al-Istifadhah". The conclusion results state that the Meulaboh Syar'iyah Court Judge is in consideration of accepting the testimony of the witness Syahadah al-Istifadah for the sake of creating a determination that creates certainty, justice for the benefit of the law for the parties, so that the desired benefits in life can be fulfilled.